Crystalline phase detection in glass ceramics by EPR spectroscopy - Antuzevics, A.; Rogulis, U.; Fedotovs, A.; Popov, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
The advances of EPR spectroscopy for the detection of activators as well as determining their local structure in the crystalline phase of glass ceramics is considered. The feasibility of d-element (Mn2+, Cu2+) and f-element(Gd3+, Eu2+) ion probes for the investigation of glass ceramics is discussed. In the case of Mn2+, the informationis obtained from the EPR spectrum superhyperfine structure, for Gd3+ and Eu2+ probes – from the EPR spectrum fine structure, whereas for Cu2+ ions the changes in the EPR spectrum shape could be useful. The examples of EPR spectra of the above-mentioned probes in oxyfluoride glass ceramics are illustrated.